School Principal Leadership Strategies in Improving the performance of Administrative Staff (IJORER : International Journal of Recent Educational Research, 2026)
This study examines the leadership strategies of a school principal in improving the performance of administrative staff at MTsN 2 Bengkulu Tengah. While previous studies have highlighted the importance of principal leadership in educational settings, limited research has specifically explored how leadership strategies are enacted to address administrative performance challenges in the context of digital transformation in madrasah. This study adopts a qualitative case study approach. Data were collected through in-depth interviews, non-participant observation, and documentation involving the principal, administrative staff, vice principals, and teachers. The data were analyzed using the Miles and Huberman model, supported by triangulation. The findings reveal four key leadership strategies: (1) competency development through targeted training and mentoring, (2) motivation enhancement through recognition and a supportive work climate, (3) continuous supervision and feedback, and (4) integration of digital technology in administrative processes. These strategies contributed to improved discipline, task efficiency, technical skills, and service quality. However, challenges remain, particularly in digital competence gaps, workload distribution, and adaptation to administrative digitalization. This study highlights the novelty of an adaptive and participatory leadership approach that integrates human resource development with digital transformation in madrasah administration. The findings offer practical implications for school leaders in designing context-sensitive strategies to strengthen administrative performance.